2014
DOI: 10.1039/c4ra03556a
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties and electrical characteristics of Ho2O3 and HoTixOy gate dielectrics for a-InGaZnO thin-film transistors

Abstract: Transfer and output characteristics of high-κ Ho2O3 and HoTixOy a-IGZO TFT devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The binding energy of pure Ho 4d is 161.8 eV. The chemical bonding of Ho–O or Ho–O–C–N makes it shift to 161.62 eV [ 35 , 36 ]. The C 1s spectra present three peaks at 282.59 eV, 283.79 eV, and 286.88 eV.…”
Section: Resultsmentioning
confidence: 99%
“…The binding energy of pure Ho 4d is 161.8 eV. The chemical bonding of Ho–O or Ho–O–C–N makes it shift to 161.62 eV [ 35 , 36 ]. The C 1s spectra present three peaks at 282.59 eV, 283.79 eV, and 286.88 eV.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 To study whether the surface roughness was a major factor influencing the TFTs performance, the root-mean-square (RMS) roughness was obtained from atomic force microscopy analysis (AFM, not shown here To investigate how the ZrO x interlayer affect the total traps, the samples were characterized by high-angle annular dark-field (HAADF) STEM and EDS. The unit-area capacitance of AlO x and ZrO x /AlO x insulators was 38 nF/cm 2 and 36 6 nF/cm 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the smooth surface of the insulator is benecial for TFT performance. 19,20 To study whether the surface roughness was a major factor inuencing the TFTs performance, the root-mean-square (RMS) roughness was obtained from atomic force microscopy analysis (AFM, not shown here). The RMS values of AlO x and ZrO x /AlO x lms are 1.98 and 1.46 nm.…”
Section: Ssmentioning
confidence: 99%
“…The detail analysis of XPS spectrum and peak postition of 4d core level reveals that the Ho cation are resent in +3 oxidation states and matches with earlier literature. [22] The XPS study revails that the observed cationic oxidation state are Co 2+ , Mn 4+ and Ho 3+ in Ho 2 CoMnO 6 .…”
Section: X-ray Photo-electron Spectroscopy (Xps)mentioning
confidence: 85%